2018
DOI: 10.1016/j.stueduc.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Promoting quality and equity in socially disadvantaged schools: A group- randomisation study

Abstract: A B S T R A C TThis study investigates the impact of the Dynamic Approach to School Improvement (DASI) on promoting quality and equity. Forty primary schools in socially disadvantaged areas were randomly split into two groups. The control group was supported to develop action plans, whereas the experimental group used DASI. To investigate the impact of DASI on quality, student achievement gains in mathematics were measured. Using multilevel analyses the experimental schools managed to promote student achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…So far, researchers in the field of EER have made use of studies searching for differential effectiveness to identify whether specific factors can be treated as generic or whether they have differential effects (see Kyriakides, 2007). By reanalysing these two effectiveness studies Kyriakides & Creemers, 2009), we argue that studies on differential teacher and school effectiveness can address issues about the relation between quality and equity and may contribute to designing school-based interventions aiming to promote both dimensions of effectiveness (Charalambous et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…So far, researchers in the field of EER have made use of studies searching for differential effectiveness to identify whether specific factors can be treated as generic or whether they have differential effects (see Kyriakides, 2007). By reanalysing these two effectiveness studies Kyriakides & Creemers, 2009), we argue that studies on differential teacher and school effectiveness can address issues about the relation between quality and equity and may contribute to designing school-based interventions aiming to promote both dimensions of effectiveness (Charalambous et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Coleman Raporu gibi önemli araştırmalarca da vurgulandığı üzere, aile ve toplumun yüksek eğitim ve gelişmişlik düzeyi, öğrenci başarısında okulun etkisini azaltırken, toplumsal gelişmişlikteki düşüş öğrenciler üzerinde okul etkisini artırmaktadır (Coleman vd., 1966;Heyneman ve Loxley, 1983). Benzer şekilde, sosyoekonomik dezavantajların öğrenciler üzerindeki etkilerinin okul içi uygulamalarla azaltılabildiğini gösteren bulgular (Charalambous, Kyriakides ve Creemers, 2018;Strand, 2014), bu konuda okul düzeyindeki politika ve uygulama alanının önemini göstermektedir. Yine araştırmalar, ilköğretimden ortaöğretime doğru ilerledikçe yani sınıf düzeyi yükseldikçe, öğrencilerin okul bağlılıklarının azaldığını ortaya koymaktadır (Bellici, 2015;Finn, 1993).…”
Section: Discussionunclassified
“…In addition, recent effectiveness studies aim to determine whether effective schools can reduce the initial differences observed in student outcomes which can be attributed to student background factors that are unlikely to change (e.g. Charalambous, Kyriakides, and Creemers 2018;Kyriakides, Creemers, and Charalambous 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…This, however, implies that the 'one-size-fits-all' approach is not effective in addressing issues of equity in education. Instead of providing the same learning opportunities to all students, it is argued that schools should provide increased learning opportunities to students who do not come from favourable backgrounds, so as to compensate for the original injustices these students may face (Charalambous, Kyriakides, and Creemers 2018;Kelly and Downey 2010). Accordingly, this type of positive discrimination is not only considered by some as acceptable, but, in fact, essential to promote equity actively in schools, especially against the backdrop of international research evidence identifying relationships between student performance and socio-economic status.…”
Section: Introductionmentioning
confidence: 99%